Evaluasi Sistem Drainase untuk Antisipasi Limpasan Debit dengan Prinsip Zero Delta Q Studi Kasus: Perumahan The Savanna Batu - Asid, Nurul Jannah; Kucaravita, Sekar Ayu; Apriliani, Rizki Astri; Ridlwan, Yusuf (Program Studi Teknik Sipil Universitas Narotama, 2024)
Batu City as one of the tourist centers in East Java Province has resulted in the need for very fast property development. The Savanna complex is currently one of the most popular among consumers. One of the things that must be considered in housing construction is the wastewater and rainwater disposal system because it concerns the comfort of residents. Housing construction on land that was originally rice fields and catchments will cause problems related to additional water runoff. Based on this, a drainage system is needed that does not increase water runoff before and after construction. The Zero Delta Q policy is a